Linking animal cruelty and family violence - Zilney, Lisa Anne (Cambria Press, 2007)
Introduction -- Theoretical foundations -- Study methodology -- Abuse of nonhumans -- Establishing a link? -- Masculinities and nonhumans -- Discussion and implications